Platelet Activation in Myeloproliferative Disorders - Cortelazzo, S; Viero, P; Barbui, T (Thrombosis and Haemostasis, 1981)
Beta-thromboglobulin (beta-TG) and platelet factor four (PF4) are specific platelet proteins released when a process of platelet activation occurs.The present study was undertaken in order to measure beta-TG and PF4 both as absolute plasma value and ratio to platelet number in 69 patients with myeloproliferative disorders (MD). The aim was to establish whether the increase of the two proteins could depend on platelet number or indicated an “in vivo” platelet activation.In 74% of patients beta-TG was found elevated and PF4 was high in 68% of cases. However in 34.7% and in 31.9% of cases respectively, the elevation of the two platelet markers was correlated to platelet number and the ratio was normal. Only in about one third of cases an “in vivo” platelet activation could be admitted and this finding provides a more rational use of antiaggregating agents.
Keywords: Myeloproliferative disorders; Platelets; Beta-thromboglobulin; Platelet factor four